1991
DOI: 10.1002/cne.903030206
|View full text |Cite
|
Sign up to set email alerts
|

Synapses made by axons of callosal projection neurons in mouse somatosensory cortex: Emphasis on intrinsic connections

Abstract: This is one of a series of papers aimed at identifying the synaptic output patterns of the local and distant projections of subgroups of pyramidal neurons. The subgroups are defined by the target site to which their main axon projects. Pyramidal neurons in areas 1 and 40 of mouse cerebral cortex were labeled by the retrograde transport of horseradish peroxidase (HRP) transported from severed callosal axons in the contralateral hemisphere. Terminals of the local axon collaterals of these neurons ("intrinsic" te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 70 publications
2
28
0
2
Order By: Relevance
“…Young adult, male CD/1 mice were anesthetized with sodium pentobarbitol (80 mg/kg), and horseradish peroxidase (HRP) was applied to the cut ends of callosal axons as described in detail previously (White and Czeiger, 1991;Czeiger and White, 1993). Three days later, the mice were anesthetized deeply with chloral hydrate and perfused with a fixative containing 4% paraformaldehyde, 0.3% glutaraldehyde, and 15% of a saturated picric acid solution in 0.1 M phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Young adult, male CD/1 mice were anesthetized with sodium pentobarbitol (80 mg/kg), and horseradish peroxidase (HRP) was applied to the cut ends of callosal axons as described in detail previously (White and Czeiger, 1991;Czeiger and White, 1993). Three days later, the mice were anesthetized deeply with chloral hydrate and perfused with a fixative containing 4% paraformaldehyde, 0.3% glutaraldehyde, and 15% of a saturated picric acid solution in 0.1 M phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…However, other data suggest that this phenomenon might be limited to high-order cortical areas. In the primary visual (Kisvárday et al, 1986;Gabbott et al, 1987;McGuire et al, 1991), somatosensory (Elhanany and White, 1990;White and Czeiger, 1991), and motor cortices (Keller and Asanuma, 1993), a lower proportion of elements postsynaptic to intrinsic axons contributed by pyramidal neurons are dendritic spines (ϳ75-90%), with no difference between proximal and distal projections.…”
Section: The Responses Of Perirhinal Cells To Neocortical Stimuli Depmentioning
confidence: 99%
“…For example, 97% of the intrinsic axon collaterals of callosally projecting pyramidal neurons in mouse visual cortex were reported to contact dendritic spines (Czeiger and White, 1993). Moreover, other investigations (Elhanany and White, 1990;White and Czeiger, 1991) in mouse somatosensory cortex have revealed that approximately 90% of intrinsic axon collaterals of both associational and callosal pyramidal neurons synapse onto dendritic spines. In contrast, the percentage of intrinsic axon projections forming excitatory synapses with dendritic spines appears to be substantially lower in other cortical systems.…”
Section: Target Specificity Of Supragranular Pyramidal Neuron Projectmentioning
confidence: 99%